An update on our ability to monitor castration-resistant prostate cancer dynamics with cell-free DNA. (3rd July 2021) - Conteduca, Vincenza; Brighi, Nicole; Conteduca, Donato; Bleve, Sara; Gianni, Caterina; Schepisi, Giuseppe; Iaia, Maria Laura; Gurioli, Giorgia; Lolli, Cristian; De Giorgi, Ugo
ABSTRACT: Introduction : Prostate cancer is one of the most frequent tumors worldwide. Due to the lack of reliable markers, patients are usually diagnosed at a late stage when it becomes castration-resistant prostate cancer (CRPC) with a worse outcome. Thus, it is essential to ameliorate the clinical management of these patients. Nowadays, the use of liquid biopsy represents a minimally invasive way to provide a complete molecular landscape of prostate cancer. Thus, this review aims to outline the clinical value of cell-free DNA in real-time monitoring of metastatic CRPC (mCRPC). Areas covered : This comprehensive review explores in detail the characteristics as well as clinical applications of plasma DNA analysis in mCRPC. Expert opinion : The assessment of circulating tumor DNA fraction is a valid and robust biomarker in mCRPC able to predict clinical outcome and monitor disease evolution during treatment. Recently, several methods (i.e. next generation sequencing and digital droplet PCR) are used to investigate genomics in cell-free DNA and novel nanotechnology-based approaches are currently under evaluation in order to improve clinical management of mCRPC patients.